Effects of insecticides intended for Ceutorhynchus napi Gyll. control in oilseed rape on ground beetles - Sivčev, Lazar; Sivčev, Ivan; Graora, Draga; Tomić, Vladimir; Dudić, Boris; Büchs, Wolfgang; Gotlin - Čuljak, Tanja (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2017)
The effects of insecticides that are commonly used for conventional and integrated oilseed rape (OSR) management on ground beetles were studied. Monitoring of harmful species showed that only insecticides intended against Ceutorhynchus napi should be applied. There were no differences in beetle numbers and phenology of settling of C. napi in the OSR fields that received different management practices. The type of OSR management has a primary and significant impact on ground beetles abundance. Early in the spring, ground beetles settled more massively on the non-tilled OSR field with abundant weed cover and mulch on soil surface. However, there were no significant differences in species richness between the OSR fields managed differently. A total of 22 species were recorded. Early in the spring, the granivorous ground beetles Amara aenea (47.3%) and Harpalus distinguendus (32.5%) were dominant. When insecticides were applied, immigration of ground beetles began, so that their adverse effect was minimal. In both management systems the number of ground beetles and their diversity increased after spraying. In conclusion, no significant harmful effects of the insecticides on ground beetles were detected in OSR fields managed in two different ways.